School entry, afternoon care and mothers' labour supply - Ludovica Gambaro; Jan Marcus; Frauke Peter (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
Most literature on the relationship between childcare availability and maternal labour force participation examines childcare for preschool aged children. Yet families must continue to arrange childcare once their children enter primary school, particularly in countries where the school day ends at lunchtime. In this paper we examine the case of Germany, a country that has moved from an exclusively half-day school system to one where formal afternoon care is increasingly available. We estimate the effect of afternoon care on maternal labour supply. To do so, we use a novel matching technique, entropy balancing, and draw on the rich and longitudinal data of the German Socio-Economic Panel (SOEP). We show that children's afternoon care increases mothers' employment rate and their working hours. To confirm the robustness of our results we conduct a series of sensitivity analysis and apply a newly proposed method to assess possible bias from omitted variables. Our findings highlight how childcare availability shapes maternal employment patterns well after school entry.
Keywords: J13; J63; J65; 330; Afternoon care; Maternal labour supply; All-day schools; Entropy balancing